Pengembangan Bahan Ajar Berbasis Komik Digital untuk Meningkatkan Kemampuan Siswa pada Materi Operasi Hitung Campuran Kelas IV Sekolah Dasar (Indo-MathEdu Intellectuals Journal, 2025)
The background of this study is based on the low interest and learning outcomes of students in mixed arithmetic operations material, as well as the lack of use of technology in teaching materials used by teachers. This study aims to develop digital comic-based teaching materials to improve students' abilities in mixed arithmetic operations material for fourth grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the study were fourth grade students of SDN 1 Gandasoli 21 students in the experimental class and the control class. The instruments used included observation, interviews, validation questionnaires, and initial and final tests. The results of the validation by material experts and media experts showed that digital comic-based teaching materials were declared very feasible to use. The implementation results showed an increase in students' abilities in solving mixed arithmetic operations problems after using digital comic-based teaching materials. Thus, the development of digital comic-based teaching materials is effective in improving elementary school students' understanding and interest in learning mathematics.